1984
DOI: 10.1002/eji.1830141208
|View full text |Cite
|
Sign up to set email alerts
|

B cell activation potential of insulin‐reactive T cells in H‐2b mice

Abstract: The murine T cell response to heterologous insulins provides a good model system for studying the mechanism of immune response (Ir)-gene function, since insulin is a small, chemically well-defined molecule. H-2b mice respond predominantly to A chain loop determinants of beef insulin, presented by the I-A epitope Ia. W39. However, using a library of insulin-specific T cell hybridomas (THy), we previously found that immunization of H-2b mice with beef insulin activates a much wider population of T cells than are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A number of studies have demonstrated that maintenance of an intact interchain disulfide linkage between the A and B chains is necessary for the effective Th response to several dominant insulin epitopes (1)(2)(3)(4)(5). However, other investigators have shown that a class II H-2-restricted Th response can be induced against both insulin A chain-and insulin B chain-derived peptides in the absence of the disulfidelinked B and A chain fragments, respectively (6)(7)(8)(9). It is tempting to speculate that the Th response to one or more of these insulin-derived peptides may be relevant to the pathogenesis of insulin-dependent (type I) diabetes mellitus (IDDM).…”
mentioning
confidence: 99%
“…A number of studies have demonstrated that maintenance of an intact interchain disulfide linkage between the A and B chains is necessary for the effective Th response to several dominant insulin epitopes (1)(2)(3)(4)(5). However, other investigators have shown that a class II H-2-restricted Th response can be induced against both insulin A chain-and insulin B chain-derived peptides in the absence of the disulfidelinked B and A chain fragments, respectively (6)(7)(8)(9). It is tempting to speculate that the Th response to one or more of these insulin-derived peptides may be relevant to the pathogenesis of insulin-dependent (type I) diabetes mellitus (IDDM).…”
mentioning
confidence: 99%
“…Insulin is a chemically well-defined peptide hormone (molecular weight, -5,000), which consists of an A and a B chain that are linked by two disulfide bridges; an intrachain disulfide bond creates a loop in the A chain which contains the amino acids at positions A7, A8, A9, and A10. Using the various species of insulin which differ at single amino acids, we were able to determine the fine specificity of our T cells (30,31,34).…”
Section: * Corresponding Authormentioning
confidence: 99%
“…Insulin is a chemically well-defined peptide hormone (molecular weight, -5,000), which consists of an A and a B chain that are linked by two disulfide bridges; an intrachain disulfide bond creates a loop in the A chain which contains the amino acids at positions A7, A8, A9, and A10. Using the various species of insulin which differ at single amino acids, we were able to determine the fine specificity of our T cells (30,31,34).To define the MHC restriction of our insulin-reactive T helper hybridoma (THy) lines precisely, we made use of the class II mutant bml2 mouse and the B6 wild type. The I-Ap gene of the bml2 mouse differs from that of the wild type at three nucleotide positions, which give rise to three amino acid changes clustered within the first extracellular domain of the Ap molecule (43).…”
mentioning
confidence: 99%
“…The following cell lines, transformed cells and hybrids were cultured in 10% fetal calf serum (FCS)/RPMI 1640 medium supplemented as described below: CTL-L (IL 2-dependent C57BL/6 anti-DBN2 CTL line [19]); EL4-16 (H-2b) thymoma [18]; ELWPG (H-2b) thymoma cells are EL4 cell variant that is sensitive to HAT-containing medium (P. Golstein, unpublished); BW5147 (H-2k) thymoma cells; L12R4 (H-2b) T lymphoma cells [20]; and two C57BLi6 anti-Ins T cell X BW5147 hybrid cell lines: 52H10Fll with specificity against the bovine Ins A chain and 51A4C10 with specificity against ungulate Ins B chains [21].…”
Section: Cellsmentioning
confidence: 99%
“…Thus, the Ins-specific Th cell clones needed about lo4-fold higher TNP-Ins concentration for induction of IL 2 release compared to the TNP-Ins concentration needed for maximal helper activity. Analysis of helper activity and IL 2 release by two Ins-specific Th cell hybridoma clones (Dr. B. Huber) showed that these cells needed the same high concentration of TNP-Ins for both induction of help and IL2 release (not shown, see [21]). On the other hand, chicken gamma-globulin (CGG)-specific T cell lines [12] and clones (unpublished) showed maximal helper activity also in the range of 1-10 ng TNP-CGG/ml for TNP-LPS primed B/ MQ, cells in the same culture system.…”
Section: Antigen Dose Requirement For Induction Of Help and Il 2 Releasementioning
confidence: 99%